Protective effect of N-acetyl cysteine on vascular function of young individuals after a bout of resistance exercise: a randomized placebo-controlled study. (3rd October 2022) - Mavraganis, G; Georgiopoulos, G; Sakelliou, A; Delialis, D; Patras, R; Sianis, A; Dimopoulou, A M; Oikonomou, E; Athanasopoulos, S; Kanakakis, I; Fatouros, I; Mitrakou, A; et al.
Abstract: Background: High intensity resistance exercise may temporarily induce vascular dysfunction mediated by pro-oxidant and pro-inflammatory pathways. Whether antioxidant supplements ameliorate this dysfunction has not been clarified. Purpose: In the present study we aimed to evaluate the effect of the antioxidant N-acetyl cysteine (NAC) on vascular function after a bout of high-intensity resistance exercise in healthy young individuals. Methods: In this randomized, cross-over, placebo-controlled study, ten healthy male volunteers (mean age 24.2±2.1 years) who exercised regularly were randomized to a daily oral administration of NAC or placebo during an 8-day recovery after an acute intense eccentric exercise protocol. In order to estimate changes in vascular parameters of interest -pulse wave velocity (PWV) and flow-mediated dilation (FMD)-, measurements were performed pre-exercise and across 6 pre-specified time points post-exercise (from 2 to 120 hours) in both arms. Blood samples were collected at baseline, immediately after exercise, 2 hours after exercise, and daily for eight consecutive days thereafter for the measurement of cellular components of the immune system. Results: Muscle exercise induced a significant decrease in FMD in the placebo arm (F=2.74, p=0.017). This phenomenon was evident until 48 hours after exercise while FMD progressively returned to baseline values thereafter. In contrast, in the NAC arm, FMD did not decrease significantly (p>0.05 for all time-points). By linear mixed model analysis, a higher increase in CD4 cells levels correlated with preserved FMD (coefficient=0.025, p=0.046) in the placebo arm whereas this association was not significant (coefficient=0.004, p=0.811) in the NAC arm. PWV did not present significant fluctuations before and after exercise in either arm (p>0.05 for all comparisons). Conclusion: A bout of eccentric exercise in young regularly training individuals induced endothelial dysfunction peaking at 48 hours, possibly partly mediated by an attenuated CD4 response. NAC exerted protective action on FMD, indicating that oxidative stress may be implicated in vivo in this setting. Funding Acknowledgement: Type of funding sources: None.